The Effect of Surface Processing on the Shear Strength of Cobalt-Chromium Dental Alloy and Ceramics - Liaisan Saleeva (Materials, 2022)
Porcelain fused to metal is widespread dental prosthetic restoration. The survival rate of metal-ceramic restorations depends not only on the qualifications of dentists, dental technicians but also on the adhesive strength of ceramics to a metal frame. The goal of the research is to determine the optimal parameters of the surface machining of the metal frame to increase the adhesion of metal to ceramics. Adhesion of cobalt-chromium alloy and ceramics was investigated. A profilometer and a scanning electron microscope were used to analyze the morphology. To estimate the adhesion the shear strength was measured by the method based on ASTM D1002-10. A method of surface microrelief formation of metal samples by plasma-electrolyte treatment has been developed. Regimes for plasma-electrolyte surface treatment were investigated according to current-voltage characteristics and a surface roughness parameter. The samples were subjected to different surface machining techniques such as polishing, milling, sandblasting (so-called traditional methods), and plasma-electrolyte processing. Morphology of the surface for all samples was studied and the difference in microrelief was shown. The roughness and adhesive strength were measured for samples either. As a result, the mode for plasma- electrolytic surface treatment under which the adhesive strength was increased up to 183% (compared with the traditional methods) was found.